Optimal post-gastroscopy timing of the urea [14C] breath test for Helicobacter pylori diagnosis: a histopathology-anchored diagnostic accuracy study - Mei Wu; Xinyuan Wang; Lijuan Wang; Yining Xiang; Liangbi Xu (Frontiers in Medicine, 2026)
Background Helicobacter pylori is a major cause of gastric carcinogenesis, and accurate detection of active infection guides eradication therapy and cancer prevention. The urea [ 14 C] breath test (UBT) is widely used, but its reliability and optimal timing when performed on the same day after gastroscopy are uncertain. Methods In this single-center retrospective diagnostic-accuracy study, 298 adults underwent gastroscopy followed by UBT at 1 hour ( n = 99), 2 hours ( n = 99), or 4 hours ( n = 100) between December 2023 and January 2025. The reference standard was defined independently of the UBT as positive immunohistochemistry, or concordant rapid urease test and methylene blue staining in immunohistochemistry-negative cases. Agreement and diagnostic-performance measures were estimated, and histopathological characteristics of false-negative results were examined. Results The reference-standard prevalence of H. pylori infection was 47.0% (140/298). Agreement was substantial to almost perfect at 1, 2, and 4 hours (κ = 0.758, 0.817, and 0.704, respectively; all P < 0.001). The 2-hour interval had the highest specificity (96.2%) and positive predictive value (95.2%), whereas the 4-hour interval had the highest sensitivity (95.6%) and negative predictive value (95.5%). All five false-negative results at 1 hour occurred in histopathological Stage III ( P = 0.044). The examined procedural and mucosal-background factors were not significantly associated with UBT accuracy. Conclusion Same-day post-gastroscopy UBT was clinically informative in this cohort. Among the evaluated intervals, 2 hours favored diagnostic confirmation, whereas 4 hours favored sensitivity-oriented screening.